DETECTING CONFIGURATION WEAKNESSES IN GEODETIC NETWORKS - Hekimoglu, S.; Erenoglu, R. C.; Sanli, D. U.; Erdogan, B. (TAYLOR & FRANCIS LTD, 2011)
In geodetic networks, probable failures in the outlier detection arise not only due to ability of outlier detection methods, but also due to the weakness in the configuration of the networks. The purpose of this paper is to detect this weakness by cross-checking the observations for existing geodetic networks or at design stage. To do it, we introduced the median equations derived from the condition equations among the observations, considering a certain number of outliers to be detected in the network in advance. Firstly the proposed method is applied on a leveling network. Then to apply the new method on all kinds of geodetic networks, a general algorithm has been developed. By using this approach, we can find the controllable or non-controllable observations in view of detecting outliers in an existing network. Thus, the results of the outlier detection methods are confirmed. Moreover, at the design stage of geodetic networks, one can decide whether the network is designed reliably prior to fieldworks. If the network configuration is found to be weak at some part, then it can be improved by adding required observation(s) to the surveying plan.
Keywords: Geodetic networks; Median equation; Reliability; Outliers; Condition equations; LEAST-SQUARES; Engineering; Geology; Remote Sensing